Effects of a Multidisciplinary Lifestyle Intervention for Obesity on Mental and Physical Components of Quality of Life: The Mediatory Role of Depression. Issue 1 (February 2013) - Pazzagli, Chiara; Mazzeschi, Claudia; Laghezza, Loredana; Reboldi, Gian Paolo; De Feo, Pierpaolo
The current study investigates the effects of a multidisciplinary lifestyle intervention for obesity on Health Related Quality of Life (HRQoL). In this study, 92 adults with obesity were weighed and completed the Short Form Health Survey (SF–36) and the Center for Epidemiologic Studies Depression Scale (CES–D) at the baseline and at the end of a 3-month intervention. Repeated measures analysis of variance (ANOVA), a series of hierarchical regressions, and the statistical mediation analysis of Baron and Kenny were conducted. (a) Over 3 months, changes in weight and the mental and physical scales of the SF–36 and depression were all significant. (b) The results indicate a significant mediation of changes in depression scores for the association between weight loss and enhancement on the General Health scale of the SF–36. Improvements to HRQoL from a multidisciplinary lifestyle intervention seem to affect both the physical and mental components of the SF–36 score and to reduce depression, contributing to enhanced self-perceptions of well-being.